The Impact of Ghana's HE Governance and Regulatory Framework on Financial Sustainability - Ayam, Justice Ray Achoanya (International Journal of African Higher Education, 2020)
Higher education governance, legal and regulatory regimes in Ghana remain an important factor in the ever-complex higher educational landscape and its attendant funding challenges. The increased global demand for higher education reforms further strengthens the importance of higher education governance, legal and regulatory framework role in assuring sustainable funding of higher education. The purpose of this study is to measure the relationship between the governance and regulatory variables influence on financial sustainability. The research work utilises quantitative research methodology with a well validated research instrument to undertake this correlational study. The study outcome revealed a statistically significant relationship between the combined effects of the variables whiles two out of the eight variables were found be significant in predicting best fit equation for financial sustainability. The research recommendations should afford higher education practitioners the opportunity to undertake relevant reforms of the current governance, legal and regulatory practices in the country.